IL-1 Receptors Mediate Persistent, but Not Acute, Airway Hyperreactivity to Ozone in Guinea Pigs - Verhein, Kirsten C. (American Thoracic Society, 2008)
Ozone exposure in the lab and environment causes airway hyperreactivity lasting at least 3 days in humans and animals. In guinea pigs 1 day after ozone exposure, airway hyperreactivity is mediated by eosinophils that block neuronal M(2) muscarinic receptor function, thus increasing acetylcholine release from airway parasympathetic nerves. However, mechanisms of ozone-induced airway hyperreactivity change over time, so that depleting eosinophils 3 days after ozone makes airway hyperreactivity worse rather than better. Ozone exposure increases IL-1β in bone marrow, which may contribute to acute and chronic airway hyperreactivity. To test whether IL-1β mediates ozone-induced airway hyperreactivity 1 and 3 days after ozone exposure, guinea pigs were pretreated with an IL-1 receptor antagonist (anakinra, 30 mg/kg, intraperitoneally) 30 minutes before exposure to filtered air or to ozone (2 ppm, 4 h). One or three days after exposure, airway reactivity was measured in anesthetized guinea pigs. The IL-1 receptor antagonist prevented ozone-induced airway hyperreactivity 3 days, but not 1 day, after ozone exposure. Ozone-induced airway hyperreactivity was vagally mediated, since bronchoconstriction induced by intravenous acetylcholine was not changed by ozone. The IL-1 receptor antagonist selectively prevented ozone-induced reduction of eosinophils around nerves and prevented ozone-induced deposition of extracellular eosinophil major basic protein in airways. These data demonstrate that IL-1 mediates ozone-induced airway hyperreactivity at 3 days, but not 1 day, after ozone exposure. Furthermore, preventing hyperreactivity was accompanied by decreased eosinophil major basic protein deposition within the lung, suggesting that IL-1 affects eosinophil activation 3 days after ozone exposure.